Feasibility of conducting a randomized, placebo-controlled study assessing whether omega-3 fatty acids prevent gout flares when starting urate-lowering treatment. Issue 3 (25th October 2022) - Abhishek, Abhishek; Fuller, Amy; Nakafero, Georgina; Zhang, Weiya; Dumbleton, Jennifer; Hawkey, Christopher; Coupland, Carol; Terkeltaub, Robert; Doherty, Michael
Abstract: Objective: The aim was to test the feasibility of a randomized controlled trial exploring whether omega-3 fatty acid supplementation limits gout flares during treat-to-target urate-lowering treatment (T2T-ULT). Methods: Adults with at least one gout flare in the past 12 months and serum urate (SU) ≥360 μmol/l were recruited from general practices (primary method) and randomly assigned 1:1 to receive omega-3 fatty acid supplementation (4 g/day) or placebo for 28 weeks. At week 5, participants began T2T-ULT. The primary outcome was drop-out rate. Secondary outcomes were recruitment rate, outcome data completeness, the number, severity and duration of gout flares between weeks 5 and 28, and study drug compliance. Results: Ninety-five per cent of randomized participants ( n  = 60) completed all study visits. The primary method recruitment rate was 2.2%. Fifty and 42 participants achieved SU < 360 and 300 μmol/l (6 and 5 mg/dl), respectively. The number of gout flares [median (interquartile range): active 1 (0–2) and placebo 1 (0–2)], flare duration [mean (s .d .): active 7.00 (4.52) days and placebo 7.06 (8.14) days] and time to first flare [hazard ratio (95% CI) 0.97 (0.50, 1.86)] were comparable between both arms. Study drug compliance was high and comparable in both arms [median (interquartile range) returned capsule count: active 57 (26–100) and placebo 58 (27–154)]; red blood cell omega-3 fatty acid index increased twofold in the active arm and remained unchanged in the control arm. Conclusion: The study demonstrated feasibility and provided useful metrics for conducting a community-based gout flare prophylaxis trial. Study registration: ISRCTN; https://www.isrctn.com/ ; ISRCTN79392964. Lay Summary: What does this mean for patients? Gout can be managed with urate-lowering medicines. However, these medicines can trigger gout flares in the initial stages of treatment. To prevent this, anti-inflammatory medicines are recommended for the first 6 months of treatment, but many people with gout cannot take them because of other health conditions and/or treatments. Omega-3 fatty acids are safe and have anti-inflammatory properties, and animal studies suggest that they might prevent gout flares. Before testing whether omega-3 fatty acids can prevent gout flares in a large clinical trial, we ran a smaller study to determine whether it would be feasible. Sixty people with gout were recruited. They took either omega-3 capsules or identical olive-oil capsules for 28 weeks and reported gout flares in a paper diary. They began urate-lowering treatment 4 weeks after starting the capsules. Most participants followed the treatment as advised, tolerated it well, and could not guess whether they were taking omega-3 or olive-oil capsules. Most flare diaries were completed fully. Three people dropped out from the study, but only 1 in 45 people approached took part. Overall, we found that it would be possible to deliver a study that examines how well omega-3 supplements prevent flares when starting urate-lowering medicine.